2017
DOI: 10.1002/acm2.12050
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of clinical feedback on image quality differences between two CT scanner models

Abstract: The aim of this work was to quantitate differences in image quality between two GE CT scanner models — the LightSpeed VCT (“VCT”) and Discovery HD750 (“HD”) — based upon feedback from radiologists at our institution. First, 3 yrs of daily QC images of the manufacturer‐provided QC phantom from 10 scanners — five of each model — were analyzed for both noise magnitude, measured as CT‐number standard deviation, and noise power spectrum within the uniform water section. The same phantom was then scanned on four of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…13 The statistical LCD measurement feature sometimes exists within CT scanners in the form of built-in tools, but it is limited to particular vendors through the operator panel. 23 In addition, the built-in software from certain vendors can only be used for particular phantoms.…”
Section: Introductionmentioning
confidence: 99%
“…13 The statistical LCD measurement feature sometimes exists within CT scanners in the form of built-in tools, but it is limited to particular vendors through the operator panel. 23 In addition, the built-in software from certain vendors can only be used for particular phantoms.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a normal pixel sound for soft tissue is 62.1 HU, while, for standard and high-goal parts, they are 31.5 and 57.5 HU, respectively, for a 1- and 32-mm section thickness. The sound level of CT images is a significant factor, compared to the location of LCD objects [ 1 , 24 ]. The outcomes do not show any noteworthy changes in the CNR values among other object estimates, down to the smallest measurable object (5 mm).…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes do not show any noteworthy changes in the CNR values among other object estimates, down to the smallest measurable object (5 mm). It was observed that the ability to identify objects depends on the differentiation standard of the object, as well as its size [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Step-by-step instructions to control undefined, minor lesions (e.g., nodules in CT lung screening) have become a significant concern.…”
Section: Discussionmentioning
confidence: 99%
“…Increased image noise impeded clinical interpretation of post‐contrast CT scans from an updated CT scanner that was recently added to a fleet of existing scanners from the same vendor. The goals of this work were to quantify and standardize image quality on the new and an existing scanner using phantom images and determine why this issue was not discovered upon acceptance testing, which used conventional techniques employing water or water‐equivalent uniform sections of phantom to quantify image noise …”
Section: Discussionmentioning
confidence: 99%
“…These advancements create challenges in harmonizing image quality and appearance from a large fleet of clinical scanners. Several groups, however, have quantified and homogenized image appearance on similar scanner models using uniform sections of water or water‐equivalent materials . At our institution, feedback from radiologists indicated that differences in image appearance and noise on a new CT scanner we recently added to our fleet impeded reading of post‐contrast scans (Fig.…”
Section: Introductionmentioning
confidence: 99%